2013
DOI: 10.1016/j.bone.2013.02.019
|View full text |Cite
|
Sign up to set email alerts
|

In vivo microdamage is an indicator of susceptibility to initiation and propagation of microdamage in human femoral trabecular bone

Abstract: Microdamage has been cited as an important element of trabecular bone quality and fracture risk, as materials with flaws have lower modulus and strength than equivalent undamaged materials. However, the magnitude of the effect of damage on failure properties depends on its tendency to propagate. Human femoral trabecular bone from the neck and greater trochanter was subjected to one of compressive, torsional, or combined compression and torsion. The in vivo, new, and propagating damage were then quantified in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 53 publications
5
23
2
Order By: Relevance
“…Compared to the study by Keaveny et al the reductions in Young’s modulus caused by the initial load in the current study are smaller (2.9–75.2% here v. 5.1–91.0% by Keaveny et al), while estimated changes in ultimate strength in the current study are larger (15.9–84.0% here v. 3.6–63.8%). Our study suggests that an applied strain of 2% would, on average, result in a reduction in Young’s modulus of 30%, which is more than double that reported in similar experiments using dense cancellous bone (12% on average in bovine cancellous bone [15] and human femoral cancellous bone [27]) and less than half that expected from regression models derived using human vertebral cancellous bone (70% on average [22]). The previous study in vertebral cancellous bone [22], however, used a definition of percent reduction in Young’s modulus based on a different portion of the reload curve explaining the larger percent reduction reported.…”
Section: 0 Discussionmentioning
confidence: 44%
See 3 more Smart Citations
“…Compared to the study by Keaveny et al the reductions in Young’s modulus caused by the initial load in the current study are smaller (2.9–75.2% here v. 5.1–91.0% by Keaveny et al), while estimated changes in ultimate strength in the current study are larger (15.9–84.0% here v. 3.6–63.8%). Our study suggests that an applied strain of 2% would, on average, result in a reduction in Young’s modulus of 30%, which is more than double that reported in similar experiments using dense cancellous bone (12% on average in bovine cancellous bone [15] and human femoral cancellous bone [27]) and less than half that expected from regression models derived using human vertebral cancellous bone (70% on average [22]). The previous study in vertebral cancellous bone [22], however, used a definition of percent reduction in Young’s modulus based on a different portion of the reload curve explaining the larger percent reduction reported.…”
Section: 0 Discussionmentioning
confidence: 44%
“…Different loading modes (compression, tension, shear) have been associated with different amounts of microdamage and reductions in mechanical performance in subsequent loading. For example, mixed mode loading (compression + shear) has been shown to cause greater reductions in stiffness and larger amounts of microdamage than a single loading mode [27] and microdamage has been shown to be more likely to propagate when the loading mode is changed [15]. Because compression loading was used for both the initial load and the reload it is likely that the effects of microdamage on subsequent biomechanical performance observed in the current study may be smaller than that expected in vivo where loading is expected to be more variable and include mixed loading modes.…”
Section: 0 Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, changes in SMI, Tb.Th., and Tb.Sp. were found that, in combination with decreased BV/TV, are known to contribute to decreased mechanical integrity of bone (Mittra et al 2005; Teo 2006; Garrison et al 2009; Wegrzyn et al 2010; Wu 2013). Similar changes were observed in animals followed for two years after ovariectomy, suggesting that architectural degradation occurs within the first year, but does not progress.…”
Section: Discussionmentioning
confidence: 99%